(untitled) (Applied Biological Research, 2023)
This study was aimed to identify and phylogenetically analyze the sarcophagid flies from Jeddah (Saudi Arabia) on the basis of mitochondrial cytochrome-C-oxidase subunit-1 (COX-1) gene. Five flesh fly samples were collected from different locations of Jeddah region. All the samples were first morphologically identified as Sarcophaga dux and confirmed on the basis of COX-1 gene amplification and sequencing techniques using universal primers LCO1490 and HCO2198. For phylogenetic analysis, 5 sequences were checked by COX-1 service on barcode of life data system (BOLD) database. To determine the phylogenetic relationships and genetic variability between 5 collected and BOLD samples, large Neighbor-joining tree comprising of the collected samples and all the available S. dux BOLD samples were constructed. The 32 most related BOLD sequences were used to construct maximum likelihood (ML) and Neighbor-joining trees. The phylogenetic analysis of COX-1 gene sequences revealed significant match with S. dux sequences from BOLD database: GQ254446 (Australia), MG780139 (India), AY879255 (China), JN869983 (Malaysia) and KC249664 (Egypt). This is the first report of the flesh fly species recorded in the Western regions of Saudi Arabia. Results indicated that the genetic diversity and phylogenetic relationship analysis of the collected S. dux samples have an important role in understanding the evolutionary processes of Sarcophaga cryptic species in Western regions of Saudi Arabia.